Comparative study of tuberculosis infection by using general fractional derivative - Manvendra Narayan Mishra; Faten Aldosari (AIMS Mathematics)
The current study examined the general fractional derivative of the fractional order in the context of an incomplete treatment of tuberculosis (TB). Utilizing the fixed-point technique and nonlinear analysis, we arrived at certain theoretical conclusions on the existence and stability of the solution. The well-known Laplace transform method was used to calculate the arithmetic output of the model under consideration. This approach depends upon an elementary principle of fractional calculus. For each case of general fractional derivative, numerical simulation was also provided, each one linked with a particular fractional order in (0, 1).